2023
DOI: 10.1021/acs.est.3c04712
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Electronic Structure Engineering of Atomically Dispersed Cobalt Catalyst in Fenton-like Reaction for Efficient Degradation of Organic Pollutants

Bingkun Huang,
Xinyi Ren,
Jian Zhao
et al.

Abstract: Currently, the lack of model catalysts limits the understanding of the catalytic essence. Herein, we report the functional group modification of model single atom catalysts (SACs) with an accurately regulated electronic structure for accelerating the sluggish kinetics of the Fenton-like reaction. The amino-modified cobalt phthalocyanine anchored on graphene (CoPc/G-NH2) shows superior catalytic performance in the peroxymonosulfate (PMS) based Fenton-like reaction with Co mass-normalized pseudo-first-order reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Differences in the size-effect-induced contribution of radical mechanisms are discussed later. Adding tert -butanol (TBA) and methyl alcohol (MeOH) showed negligible inhibitory effects on SIZ degradation in all catalytic systems, and the absence of O 2 •– collectively verified the dominant role of nonradical pathways. , Furfuryl alcohol (FFA), a specific inhibitor of 1 O 2 , was added to the CoSA/PMS system and SIZ degradation declined, demonstrating the critical role of 1 O 2 . 2,2,6,6-Tetramethyl-4-piperidinyloxyl (TEMP) was employed to capture 1 O 2 in electron paramagnetic resonance (EPR) analysis. , The 1 O 2 intensity of the CoSA/PMS system was nearly 11.2 times stronger than that of the NC/PMS system, indicating that introducing Co–N 4 active sites enhanced the generation of 1 O 2 tremendously (Figure g).…”
Section: Resultsmentioning
confidence: 86%
“…Differences in the size-effect-induced contribution of radical mechanisms are discussed later. Adding tert -butanol (TBA) and methyl alcohol (MeOH) showed negligible inhibitory effects on SIZ degradation in all catalytic systems, and the absence of O 2 •– collectively verified the dominant role of nonradical pathways. , Furfuryl alcohol (FFA), a specific inhibitor of 1 O 2 , was added to the CoSA/PMS system and SIZ degradation declined, demonstrating the critical role of 1 O 2 . 2,2,6,6-Tetramethyl-4-piperidinyloxyl (TEMP) was employed to capture 1 O 2 in electron paramagnetic resonance (EPR) analysis. , The 1 O 2 intensity of the CoSA/PMS system was nearly 11.2 times stronger than that of the NC/PMS system, indicating that introducing Co–N 4 active sites enhanced the generation of 1 O 2 tremendously (Figure g).…”
Section: Resultsmentioning
confidence: 86%
“…The Fenton reaction (Fe­(II) and H 2 O 2 ) has attracted great attention in water treatment research owing to its high reaction rate, low toxicity, and mild reaction conditions. Fe­(II) can react with H 2 O 2 to produce the highly active hydroxyl radical ( • OH; eq ) which can powerfully oxidize most organic contaminants in a nonselective manner due to its high oxidation capability ( E 0 ( • OH/OH – ) = 2.73 V), , while Fe­(III) produced in situ can regenerate Fe­(II) by oxidizing H 2 O 2 (eq ). However, the reaction rate constant of H 2 O 2 -induced Fe­(III) reduction (eq , k = 9.1 × 10 –7 M –1 ·s –1 ) is 8 orders of magnitude smaller than that of H 2 O 2 -induced Fe­(II) oxidation ( k = 40–80 M –1 ·s –1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based single-atom catalysts (SACs) have aroused increasing interest in the fields of wastewater treatment and environmental remediation in the past few years due to their merits of exceptional atomic utilization, high selectivity, and structural stability. In addition, SACs can be used to establish ideal catalytic systems to investigate the interactions between the reactant molecules and the active sites of isolated metal atoms on catalyst surfaces. It has been widely reported that such catalysts could exhibit excellent removal performance of aqueous pollutants through modulating the catalytic reaction pathways in the Fenton-like systems, e.g., radical and nonradical pathways. The remarkable catalytic performance of the carbon-based SACs in Fenton-like reactions can also inspire their extended application in other AOP systems.…”
Section: Introductionmentioning
confidence: 99%